Faux Pas Recognition Test: transcultural adaptation and evaluation of its psychometric properties in Brazil. Issue 5 (3rd September 2021) - Watanabe, Rafael Gustavo Sato; Knochenhauer, Andre Enoch; Fabrin, Miguel Angelo; Siqueira, Heloise Helena; Martins, Hayrã Felipe; Oliveira Mello, Cindi Danielle de; Zingano, Bianca de Lemos; Botelho, Mariana Francisco; Yacubian, Elza Márcia Targas; Oliveira Filho, Getulio Rodrigues de; Melo, Hiago Murilo; Walz, Roger; et al.
ABSTRACT: Introduction: Many neuropsychiatric and neurodegenerative disorders produce Theory of Mind impairment. We aimed to implement a Brazilian Portuguese version of the Faux Pas Recognition Test (FPRT) and evaluate its psychometric properties. Methods: We first completed an English-Brazilian Portuguese translation and adaptation to obtain an FPRT Brazilian Portuguese version. We performed a multicentric study with 153 healthy participants (68.6% women), mean age of 38.8 years (SD = 14.6) and 12.9 years of schooling (SD = 4.5). Linear regression analysis was performed to evaluate the association of social class, age, schooling, and FPRT scores. The psychometric analyses comprised item analysis, exploratory factor analysis, reliability, and validity analysis. Results: Normative data in a Brazilian population is presented. A positive correlation of scores with years of schooling, social class, and an inverse relation with age was found. The exploratory factorial analysis found a two-component structure, one component, consisting of questions 1 through 6 ( Eigenvalue 5.325) and another component, consisting of questions 7 and 8 ( Eigenvalue 1.09). Cronbach's alpha of the 20 stories was .72. All control stories had a poor discriminative index. Conclusion: The FPRT Brazilian Portuguese version demonstrated good internal consistency and, psychometric properties and is adequate for use even in lower educational contexts in Brazil.